2007
DOI: 10.1128/jvi.02489-06
|View full text |Cite
|
Sign up to set email alerts
|

Induction of Antiviral Cytidine Deaminases Does Not Explain the Inhibition of Hepatitis B Virus Replication by Interferons

Abstract: Interferons (IFNs) play a major role in the control of hepatitis B virus (HBV), whether as endogenous cytokines limiting the spread of the virus during the acute phase of the infection or as drugs for the treatment of its chronic phase. However, the mechanism by which IFNs inhibit HBV replication has so far remained elusive. Here, we show that type I and II IFN treatment of human hepatocytes induces the production of APOBEC3G (A3G) and, to a lesser extent, that of APOBEC3F (A3F) and APOBEC3B (A3B) but not that… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
56
0

Year Published

2008
2008
2016
2016

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 48 publications
(61 citation statements)
references
References 73 publications
5
56
0
Order By: Relevance
“…However, because APOBEC3G is not efficiently induced in HepG2 cells by either IFN-␣ or IFN-␥ (Fig. 2B), in conjunction with the previous reports showing that APOBEC3G is not an essential effector in the IFN-elicited anti-HBV response (35,51), its role in mediating the antiviral effects of IFNs against HBV remains unclear.…”
Section: Discussionmentioning
confidence: 65%
“…However, because APOBEC3G is not efficiently induced in HepG2 cells by either IFN-␣ or IFN-␥ (Fig. 2B), in conjunction with the previous reports showing that APOBEC3G is not an essential effector in the IFN-elicited anti-HBV response (35,51), its role in mediating the antiviral effects of IFNs against HBV remains unclear.…”
Section: Discussionmentioning
confidence: 65%
“…Members of the APOBEC3 family of cytidine deaminases, which have been shown to target a wide range of retroviruses, were reported to inhibit HBV replication (1,26,27,38,45). Whether these enzymes are the main mediators of the action of IFNs on HBV remains controversial (21,32). Recently, TRIM22 was reported to be expressed in response to IFNs and displayed anti-HBV activity both in vitro and in vivo, but it is uncertain whether TRIM22 would displays such an activity at physiological levels (7).…”
Section: Discussionmentioning
confidence: 99%
“…Although it has been reported that these proteins also have activity against HBV, they are not primarily responsible for the anti-HBV activity of IFNs. Thus, HIV vif, even when used in combination with RNA interference to specific APOBEC3 proteins, does not abrogate the inhibitory effect of IFN on HBV (Jost et al, 2007).…”
Section: General Considerations Of How Viruses Evade the Ifn Responsementioning
confidence: 95%